Infection With Escherichia Coli Pathotypes Is Associated With Biomarkers of Gut Enteropathy and Nutritional Status Among Malnourished Children in Bangladesh - Md. Amran Gazi; Md. Ashraful Alam; Shah Mohammad Fahim; Barbie Zaman Wahid; Shaila Sharmeen Khan; Md. Ohedul Islam; Md. Mehedi Hasan; S. M. Tafsir Hasan; Subhasish Das; Subhasish Das; Mustafa Mahfuz; Mustafa Mahfuz; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Escherichia coli (E. coli) pathotypes are the most common cause of diarrhea, especially in developing countries. Environmental Enteric Dysfunction (EED) is presumed to be the result of infection with one or more pathotypes and can affect intestinal health and childhood growth. We sought to investigate the association of E. coli pathotypes infection with biomarkers of EED and nutritional status among slum-dwelling malnourished children in Bangladesh. This study comprised a total of 1050 stunted and at risk of stunting children. TaqMan Array Card assays were used to determine the presence of E. coli pathotypes in feces. Prevalence of infection with EAEC was highest (68.8%) in this cohort of children, followed by EPEC (55.9%), ETEC (44%), Shigella/EIEC (19.4%) and STEC (3.2%). The levels of myeloperoxidase and calprotectin were significantly higher in EAEC (P=0.02 and P=0.04), EPEC (P=0.02 and P=0.03) and Shigella/EIEC (P=0.05 and P=0.02) positive participants while, only calprotectin was significantly higher in ETEC (P=0.01) positive participants. Reg1B was significantly higher in participants with EAEC (P=0.004) while, neopterin levels were significantly lower in ETEC (P=0.003) and Shigella/EIEC (P=0.003) positive cases. A significant positive relationship was observed between EAEC and fecal levels of Reg1B (β = 0.28; 95% CI = 0.12, 0.43; p-value<0.001). Besides, ETEC was found to be positively and significantly associated with the levels of calprotectin (β = 0.14; 95 percent CI = 0.01, 0.26; p-value=0.037) and negatively with neopterin (β = -0.16; 95% CI = -0.30, -0.02; p-value=0.021). On the other hand, infection with EPEC was found to be negatively associated with length-for-age (β = -0.12; 95% CI = -0.22, -0.03; p-value=0.011) and weight-for-age (β = -0.11; 95% CI = -0.22, -0.01; p-value=0.037). The study findings suggest that infection with certain E. coli pathotypes (EAEC and ETEC) influences gut health and EPEC is associated with linear growth and underweight in Bangladeshi children.